Democratic Republic of Sao Tome and Principe : Request for a Three-Year Arrangement Under the Extended Credit Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The Democratic Republic of Sao Tome and Principe shows prudence in maintaining its fiscal stance assisted by the IMF extended credit facility (ECF). The authorities aim to concentrate on maintaining macroeconomic stability even though debt distress owing to a narrow export base and other issues loom as threats. Focus is on strengthening of existing monetary and public finances policies, banking supervision, and anti-money laundering, which will help in reducing poverty. Revenue from oil production is also expected to help achieve the target by 2015.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet